Spatial foraging in free ranging bearded sakis: Traveling salesmen or Lévy walkers?. Issue 5 (28th October 2013) - Shaffer, Christopher A.
Abstract According to optimal foraging theory and most current models of primate socioecology, primate foraging involves a series of decisions concerning when is the most optimal time to leave a food patch, how to travel to the next patch in an efficient manner, and how to minimize the time and distance traveled to all patches throughout the course of the day. In this study, I assess how bearded sakis solve these challenges by presenting data on their patch use, distance minimization, and by comparing their movements with non‐deterministic foraging patterns. The study group, composed of 38 ± 15 individuals, fed significantly longer in higher quality patches (quality defined by patch size and productivity) and in those that contained ripe fruit pulp. However, group size was not a significant predictor of patch occupancy. Bearded sakis traveled relatively directly between food patches, sometimes over distances > 300 m. In addition, they chose the optimal daily path among all patches visited on 9 of 17 occasions, and on average traveled only 21% more than the least distance route. Bearded saki step lengths were consistent with a Brownian rather than a Lévy Walk pattern while waiting times were consistent with a Lévy pattern. However, the distribution of their turning angles indicated a high degree of directional persistence between patches. These results suggest that bearded sakis exploit food patches that are randomly distributed spatially but heterogenous in patch quality. They appear to encode the locations of high quality food patches and minimize travel between them, despite opportunistically feeding from more abundant and randomly distributed, lower quality patches en route. Am. J. Primatol. 76:472–484, 2014. © 2013 Wiley Periodicals, Inc.